Research on Frequency of Application with Modern Chinese Herbal Medicine - 蔡永敏 何阳 邱彤 邹杰 孙大鹏 彭青鹤 贾润霞 赵会茹 贾润霞 赵会茹 (Chinese journal of integrative medicine, 2011)
Objective：To study the relationship between 500 kinds of commonly used Chinese herbal medicine and the classification of their efficacies in Chinese Materia Medica in relation to the common diseases listed in Internal Medicine.Methods：Database retrieval frequency of the quantitative statistical method was adopted.First,the 8 980 kinds of Chinese herbal medicine recorded in Chinese Materia Medica were used as the original search objects,and 4 493 kinds which were cited in more than five articles were picked out and then rechecked for further title citations.Second,as judged based on the Criterion,the numbers of articles which included the medicines in the line of standards were examined.As a result,500 species of Chinese herbal medicine were singled out based on their retrieval frequency and were then used for compilation of the classification statistics according to their efficacy and the common diseases in Internal Medicine.Results：From the classification of Chinese medicines,herbs with wide efficiency and a meek nature had higher frequencies, but those which were not appropriate as decoctions had relatively lower frequencies.However,according to the average frequency,the Chinese herbal medicine for nourishing qi and tonifying blood,at 36 346 times and 34 544 times,respectively,were the most commonly used.Analyzed from the frequency of application of the Chinese medicine in the treatment of common diseases,most of the top 10 kinds of Chinese herbal medicine with the highest frequencies generally coincided with the 500 selected medicines.In addition,the Chinese medicines with clear pharmacological efficiency were easily isolated and purified to be made into injections, although other forms are more commonly used.Conclusion：The results of the research objectively reflected the current applications of Chinese herbal medicine,and could be used as references in teaching,research,clinical applications,and in compiling and increasing the drugs in textbooks and Pharmacopoeia.